Microvascular Replantation of Totally Avulsed Scalps: Failures and Successes. Issue 2 (March 2020) - Jiang, Liangfu; Jones, Salazar; Wu, Zhipeng; Xue, Jixin; Jia, Xiaofeng
Abstract : Abstract: Total scalp avulsion is a rare but devastating injury currently without proven reconstructive techniques. While microsurgical anastomosis procedures have advanced and allowed for the replantation of digits and limbs, special anatomical considerations and risk of fatal blood loss add to the difficulty of replanting totally avulsed scalps. The authors present their replantation experience of 4 totally avulsed scalps between 2008 and 2017. Despite meticulous reconstructive techniques with proven success in limb and digit replantation, the first 3 cases failed due to various factors (i.e., thrombosis, venous congestion, reavulsion), and with experience, the fourth case was successful. Since total scalp avulsions are rare injuries, case reports are scarce, with only few publications commenting on failures which hold crucial information for surgeons to avoid pitfalls and optimize techniques. In this article, we highlight our experience with both successful and failed replantation of totally avulsed scalps, and offer recommendations and insight for optimization of this rare procedure. Abstract : Supplemental Digital Content is available in the text